A photoresist positive patterning method based on pre-exposure control

CN122613648BActive Publication Date: 2026-10-13NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611104084.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-13
Estimated Expiration
2046-07-24

AI Technical Summary

Technical Problem

[0008]针对现有金属有机光刻胶在极紫外(EUV)和电子束(EBL)曝光下普遍呈现负性光刻行为,且其实现正性光刻往往依赖添加剂和极窄的工艺窗口控制、导致分辨率和生产效率下降的技术问题,本发明提供了一种基于预曝光控制的光刻胶正性图案化方法

Benefits of technology

(1)本发明建立在对已知物质采用了特定的纯物理/光学时序操控,利用低能紫外光引发双键反应构建预交联网络,随后利用高能束(EBL/EUV)引发化学键断裂产生低极性小分子碎片以恢复其溶解性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122613648B_ABST
    Figure CN122613648B_ABST
Patent Text Reader

Abstract

The application relates to the fields of semiconductor micro-nano manufacturing and advanced photolithography technology, and discloses a photoresist positive patterning method based on pre-exposure control, which comprises the following steps: step 1, thin film preparation: dissolving antimony-based metal organic compounds containing photosensitive unsaturated double bond ligands in a coating solvent, coating on the surface of a substrate, and forming a photoresist thin film after baking treatment; the antimony-based metal organic compounds include mononuclear antimony complexes or antimony-containing metal oxygen clusters. A low-energy ultraviolet light is used to initiate a double bond reaction to construct a pre-crosslinking network, and then a high-energy beam (EBL / EUV) is used to initiate chemical bond fracture to generate low-polarity small molecule fragments to restore the solubility; through the regulation of the pure process timing, the bottom layer material, the ultraviolet pre-exposure step and the high-energy beam deconstruction step are bound, and the inversion from negative photolithography to positive photolithography is successfully realized in a single-component metal organic system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of semiconductor micro / nano manufacturing and advanced photolithography technology, specifically to a positive patterning method for photoresist based on pre-exposure control. Background Technology

[0002] As Moore's Law continues to advance, the critical dimensions of integrated circuits (ICs) have entered the single-digit nanometer node. Traditional chemical amplification photoresists, due to the unavoidable acid diffusion effect, face a severe "RLS balance" bottleneck in terms of resolution, line edge roughness, and sensitivity, and their etching resistance is gradually failing to meet the requirements of advanced semiconductor processes.

[0003] Against this backdrop, metal-organic lithography (MORs), such as nanoclusters or coordination compounds containing metal cores of tin, titanium, zirconium, hafnium, zinc, and antimony, have become a key research direction for next-generation EUV / EBL high-resolution lithography technology due to their extremely high absorption cross-sections for high-energy beams such as extreme ultraviolet (EUV) and electron beam (EBL), which theoretically maintain high metal density and are expected to have good etching resistance potential. Furthermore, after development, they can form metal oxide networks with ultra-high etching resistance.

[0004] However, existing metal-organic photoresist systems face significant technical bottlenecks in practical processes: most metal-organic photoresists, under electron beam or EUV exposure, mainly undergo ligand removal or metal center aggregation, thus exhibiting cross-linked and insoluble "negative-tone" behavior in the developer. For example, the tin-oxygen cluster-based (Organotin Oxide Hydroxide) metal-organic photoresist system disclosed in patent document US10228618B2.

[0005] In many key processes of semiconductor manufacturing (such as etching of contact holes and fabrication of dark-field masks), the industry has an irreplaceable and rigid demand for positive photoresists. Negative photoresists not only have poor flexibility in specific layout designs, but the cross-linked metal oxide network is also extremely difficult to remove with conventional solvents, seriously affecting the yield and compatibility of production lines.

[0006] To achieve "positive lithography" in metal-organic systems, conventional methods typically require altering the chemical composition of the substrate. For example, this involves adding large amounts of additives (such as Lewis bases) to the system to reduce cluster aggregation, or designing ligands with extremely complex dissociative groups. While these methods can achieve polarity reversal, they introduce several significant drawbacks: first, additives dilute the effective metal density in the photoresist film, reducing EUV absorption and etching resistance; second, the complex chemical reactions can trigger severe degassing effects, easily contaminating expensive exposure equipment lenses; and third, the process window is extremely narrow, making yield control difficult.

[0007] Therefore, the current field of advanced semiconductor lithography urgently needs a completely new process approach: that is, to achieve a controllable reversal of the polarity of high-resolution photoresist from "negative" to "positive" through purely physical and optical process control, without changing the composition of the main metal-organic compound of the photoresist or adding any additional additives. This would not only preserve the high etching resistance of metal-organic photoresists but also greatly simplify the formulation and broaden the process window. Summary of the Invention

[0008] To address the common problem that existing metal-organic photoresists exhibit negative lithography behavior under extreme ultraviolet (EUV) and electron beam (EBL) exposures, and that achieving positive lithography often relies on additives and extremely narrow process windows, leading to reduced resolution and production efficiency, this invention provides a method for positive patterning of photoresists based on pre-exposure control. This method requires no changes to the metal-organic substrate formulation or the addition of any additives; it effectively reverses the system polarity from negative to positive simply by controlling the timing of pre-exposure and patterning exposure in the photolithography process, thus obtaining high-resolution positive lithographic patterns.

[0009] This invention provides the following technical solution: a method for positive patterning of photoresist based on pre-exposure control, comprising the following steps: Step 1, Thin film preparation: An antimony-based organometallic compound containing a photosensitive unsaturated double bond ligand is dissolved in a coating solvent, coated onto the substrate surface, and then baked to form a photoresist film; the antimony-based organometallic compound includes mononuclear antimony complexes or antimony-containing metal oxygen clusters; Step 2, Pre-exposure treatment: The photoresist film is fully pre-exposed using ultraviolet light with a wavelength in the range of 254nm to 400nm, which triggers the photosensitive unsaturated double bond ligand to undergo a photochemical reaction and form a pre-crosslinked network in the film, making the film substantially insoluble in non-polar developer. Step 3, High-energy beam exposure processing: A high-energy beam is used to expose a specific patterned area of ​​the photoresist film that has undergone the pre-exposure processing, so that the exposed area regains its solubility in the non-polar developer; the high-energy beam is an electron beam; or the high-energy beam is extreme ultraviolet light; Step 4, Development: The film exposed by the high-energy beam is developed using a non-polar developer. The areas exposed by the high-energy beam are dissolved, while the areas not exposed by the high-energy beam are retained, thereby obtaining a positive photolithography pattern.

[0010] Preferably, the photosensitive unsaturated double bond ligand is a carboxylic acid ligand containing a carbon-carbon double bond.

[0011] Preferably, the carboxylic acid ligand containing a carbon-carbon double bond is selected from one or more of trans-cinnamic acid, methacrylic acid, acrylic acid, p-vinylbenzoic acid, crotonic acid, sorbic acid, furanylacrylic acid, or methoxycinnamic acid.

[0012] Preferably, the antimony-based organometallic compound is selected from one or more of the following: mononuclear antimony complex Ph3Sb(CA)2, binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 or tetranuclear antimony oxide cluster (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2.

[0013] Preferably, in step 1, the coating solvent is selected from one or more of methanol, isopropanol, N,N-dimethylformamide, acetone, ethyl acetate, propylene glycol methyl ether acetate, chloroform, cyclohexanone, or tetrahydrofuran.

[0014] Preferably, in step 1, the concentration of the antimony-based organometallic compound in the coating solvent is 15–100 mg / mL.

[0015] Preferably, in step 1, the spin coating speed is 500-5000 rpm and the spin coating time is 20-60 s; The baking process is carried out at a temperature of 80–150°C for 30–90 seconds.

[0016] Preferably, in step 2, the first wavelength is 254nm ultraviolet light, and the irradiation intensity is 50–200mW / cm². 2 The irradiation time is 0.1–0.5 hours; The first wavelength is 365nm ultraviolet light, and the irradiation intensity is 200-800mW / cm². 2 The irradiation time is 0.5 to 3 hours.

[0017] Preferably, in step 3, when the high-energy beam is an electron beam, the exposure dose of the electron beam is 100–2000 μC / cm. 2 ; The wavelength of the extreme ultraviolet light is 13.5 nm.

[0018] Preferably, in step 4, the nonpolar developing solution is selected from aliphatic hydrocarbon solvents, including one or more of n-heptane, n-nonane, or cyclopentane; The development time is 10–120 seconds.

[0019] The present invention has the following beneficial effects: (1) This invention is based on the use of specific pure physical / optical timing manipulation of known substances, using low-energy ultraviolet light to initiate double bond reactions to construct a pre-crosslinked network, and then using high-energy beams (EBL / EUV) to initiate chemical bond breaking to generate low-polarity small molecule fragments to restore their solubility. By controlling the pure process timing, the underlying material, UV pre-exposure step, and high-energy beam deconstruction step are bound together, and the reversal from negative lithography to positive lithography is successfully achieved in a single-component metal-organic system.

[0020] (2) The present invention adopts a pure single-component system without the need to add any additives, which fundamentally eliminates the problem of uneven photochemical reaction caused by uneven dispersion of additives during photolithography. This is the underlying logic of the present invention to achieve extremely high resolution, thus possessing the intrinsic advantages of greatly improving pattern resolution and reducing line edge roughness.

[0021] Meanwhile, the single-component system maintains extremely high metal density in the pre-crosslinked state, and its dry etching selectivity is significantly better than that of traditional commercial polymer photoresists (such as PMMA), ensuring that the photoresist pattern has excellent pattern transfer fidelity and superior etching resistance in the subsequent plasma etching process of semiconductor manufacturing.

[0022] (3) This polarity reversal method is not limited to a specific single molecule, but is widely applicable to metal-centered clusters with surface-modified photosensitive unsaturated ligands. The entire development process uses environmentally friendly, low-toxicity, low-polarity alkane solvents, with high process tolerance and easy to be seamlessly compatible with existing advanced semiconductor process lines.

[0023] (4) High-resolution positive patterns with feature linewidths as low as 36nm can be obtained under electron beam exposure, which has the potential to meet the stringent requirements of advanced semiconductor processes. Attached Figure Description

[0024] Figure 1 This is a schematic diagram comparing the process flow of a photoresist positive patterning method based on pre-exposure control provided by the present invention with that of a conventional direct exposure process.

[0025] Figure 2This is an AFM stepwise test graph showing the relationship between exposure dose and resist height after the mononuclear antimony complex Ph3Sb(CA)2 thin film was pre-exposed at 365nm and then subjected to electron beam exposure, as shown in Example 1.

[0026] Figure 3 This is the normalized positive electron beam exposure dose response curve corresponding to Example 1.

[0027] Figure 4 This is an atomic force microscope (AFM) image of the high-resolution positive photolithographic pattern obtained in Example 1.

[0028] Figure 5 The AFM step chart shows the relationship between exposure dose and resist height after electron beam exposure of the unexposed Ph3Sb(CA)2 film in Comparative Example 1.

[0029] Figure 6 This is the normalized negative electron beam exposure dose response curve corresponding to Comparative Example 1.

[0030] Figure 7 This is an atomic force microscope (AFM) image of the high-resolution negative lithographic pattern obtained in Comparative Example 1.

[0031] Figure 8 This is an AFM stepwise test graph showing the relationship between exposure dose and resist height after the binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 thin film was pre-exposed at 254nm and then subjected to electron beam exposure, in Example 2.

[0032] Figure 9 This is the normalized positive electron beam exposure dose response curve corresponding to Example 2.

[0033] Figure 10 This is the AFM image of the high-resolution positive lithography pattern obtained in Example 2.

[0034] Figure 11 This is an AFM stepwise test graph showing the relationship between exposure dose and resist height after the binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 thin film was pre-exposed at 365nm and then subjected to electron beam exposure, as shown in Example 3.

[0035] Figure 12 This is the normalized positive electron beam exposure dose response curve corresponding to Example 3.

[0036] Figure 13 This is the AFM image of the high-resolution positive lithography pattern obtained in Example 3.

[0037] Figure 14The AFM step chart shows the relationship between exposure dose and resist height after electron beam exposure of the unexposed binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 thin film in Comparative Example 2.

[0038] Figure 15 This is the normalized negative electron beam exposure dose response curve for Comparative Example 2.

[0039] Figure 16 The image shows the high-resolution negative lithography pattern AFM image obtained in Comparative Example 2.

[0040] Figure 17 This is an AFM stepwise test graph showing the relationship between exposure dose and resist height after the tetranuclear antimony oxide cluster (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2 thin film was pre-exposed at 254nm and then subjected to electron beam exposure, as shown in Example 4.

[0041] Figure 18 This is the normalized positive electron beam exposure dose response curve corresponding to Example 4.

[0042] Figure 19 This is the AFM image of the high-resolution positive lithography pattern obtained in Example 4.

[0043] Figure 20 The AFM stepwise test plot shows the relationship between exposure dose and resist height after electron beam exposure of the unexposed tetranuclear antimony oxide cluster (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2 thin film in Comparative Example 3.

[0044] Figure 21 This is the normalized negative electron beam exposure dose response curve for Comparative Example 3.

[0045] Figure 22 The image shows the high-resolution negative lithography pattern AFM pattern obtained in Comparative Example 3. Detailed Implementation

[0046] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0047] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0048] In this invention, the terms "comprising," "including," or "containing" indicate an open-ended inclusion relationship, meaning that other unspecified elements or steps are not excluded. When numerical ranges are involved in this invention, "about" or "approximately" means that the value is allowed to have a range of error generally accepted in the art, typically ±10% of the value.

[0049] In this invention, "pre-crosslinking" refers to the process in which the photosensitive double bond ligands inside the photoresist film undergo photochemical addition or isomerization polymerization reactions after being exposed to low-energy ultraviolet light, resulting in a sudden change in the macroscopic solubility of the film.

[0050] In this invention, "substantially insoluble" means that after the film has undergone pre-crosslinking treatment, when it is developed according to the conditions of this invention (non-polar developer, development time as described in this invention), its thickness loss is significantly less than that of the film without pre-crosslinking treatment under the same conditions (see the negative and soluble characteristics of the unexposed films under the same development conditions in the comparative examples of this invention). That is, the pre-crosslinked film remains intact as a whole and can be used as a photoresist mask layer for subsequent high-energy beam patterning, rather than requiring the film to not undergo any molecular-level swelling or trace dissolution in the developer.

[0051] In this invention, "nonpolar developer" refers to an organic solvent with a low dielectric constant at room temperature, mainly composed of carbon and hydrogen elements, which includes straight-chain, branched-chain, or cyclic aliphatic hydrocarbons (such as n-heptane, n-nonane, cyclopentane, etc.).

[0052] In this invention, "positive lithography" refers to the lithographic behavior in which the exposed area dissolves in the developer while the unexposed area remains; "negative lithography" is the opposite.

[0053] In this invention, "high-energy beam" specifically refers to a radiation beam with sufficient energy to directly break the Sb-O bonds or carbon-carbon double bond cross-linking structure in the pre-crosslinked network. Within the framework of this invention, the proven implementation of the high-energy beam is the electron beam (EBL), and extreme ultraviolet light (EUV) is the intended applicable form, thereby providing sufficient energy to restore the solubility of the exposed area.

[0054] The exposure chemical mechanisms of EUV lithography (wavelength 13.5nm) and electron beam lithography have been proven by the industry to be highly equivalent: after EUV photons are incident on the photoresist film, a large number of secondary electrons are generated mainly through the photoelectric effect and Auger process, and then the chemical bonds are broken by these secondary electrons. The energy deposition and chemical bond breaking paths are highly similar to those of electron beam exposure. Based on this known physicochemical equivalence, those skilled in the art can reasonably expect that the pre-crosslinking-de-crosslinking patterning mechanism described in this invention is also applicable to EUV exposure conditions at a wavelength of 13.5 nm, with the only difference being in process parameters such as exposure dose sensitivity.

[0055] The general operating methods and testing equipment involved in the various embodiments and comparative examples of this invention are as follows: Material sources: The antimony-containing organometallic mononuclear, binuclear, and tetranuclear cluster compounds involved were all prepared by conventional coordination chemistry synthesis methods (or purchased from commercial channels). The coating solvent and non-polar developer were commercially available chromatographic or electronic grade reagents, without further purification.

[0056] Thin film preparation equipment: A spin coater is used to spin-coat a clean silicon wafer substrate, and a precision constant temperature heating plate is used for pre-baking.

[0057] UV pre-exposure equipment: Uses a UV light source (UVlamp) with a standard wavelength of 254nm or 365nm for full-scale exposure.

[0058] High-energy beam exposure system: This embodiment uses an electron beam lithography (EBL) machine for high-resolution patterning exposure, sets a specific accelerating voltage (e.g., 30kV), and applies an array gradient exposure dose to obtain a dose response curve. It should be noted that those skilled in the art will understand that although the embodiments of this invention have been verified using electron beam (EBL), based on the equivalence of the physical mechanism of secondary electron fragmentation, the pre-crosslinking patterning method of this invention is also expected to be applicable to EUV lithography.

[0059] Atomic Force Microscopy (AFM) Characterization and Evaluation: After development, the surface morphology of the developed pattern was scanned using an atomic force microscope in Tapping Mode. By scanning a large-area exposure array, the change in resist height as a function of dose was obtained, and a "normalized electron beam exposure dose curve" was plotted to extract the sensitivity parameter. By scanning a high-density line array, the limiting characteristic linewidth (resolution) of the pattern was obtained.

[0060] Please see Figure 1 , Figure 1 The diagram illustrates a comparison between the photoresist positive patterning method based on pre-exposure control provided by this invention and the conventional direct exposure process.

[0061] In combination with the aforementioned technical solutions, such as Figure 1 As shown, the specific implementation logic of the patterning process flow (positive route in the figure) of the present invention is as follows: First, an antimony-based complex or metal-oxygen cluster (organic metal compound) containing a photosensitive double bond ligand is spin-coated onto a substrate and pre-baked to form a film; Subsequently, the key control method of the present invention is introduced—using a first wavelength light source (ultraviolet light) to fully pre-expose the film, triggering a double bond cross-linking reaction to construct an initial "pre-cross-linked network," so that the film macroscopically becomes insoluble in the non-polar developer; Next, a patterning and deconstruction process is performed. The thin film is exposed in a region using a high-energy beam (such as EBL or EUV). The high-energy beam will cause the chemical bonds in the exposed region to break, generating low-polarity small molecule fragments, so that the exposed region regains its solubility in the non-polar developer. Finally, the exposed areas are washed away using a non-polar aliphatic hydrocarbon developer, while the unexposed areas are retained because they remain in a pre-crosslinked state, thus achieving polarity reversal and obtaining a high-resolution positive pattern.

[0062] In comparison, Figure 1 The paper also demonstrates a conventional resist process route (negative route in the figure): after spin coating of the thin film, the UV pre-exposure step is skipped and high-energy beam patterning exposure is performed directly.

[0063] Due to the lack of support from the pre-crosslinked network, high-energy electrons directly induce conventional radiation crosslinking and aggregation in the system, which is ultimately retained as an insoluble substance in the exposed area after development, exhibiting traditional negative lithography behavior.

[0064] Example 1: Positive patterning process of mononuclear antimony complex Ph3Sb(CA)2 (method of this invention) (1) Thin film preparation: The mononuclear antimony complex Ph3Sb(CA)2 containing photosensitive double bond ligands was dissolved in PGMEA to prepare a coating solution with a concentration of 20 mg / mL.

[0065] The solution was evenly spin-coated onto a clean silicon wafer using a spin coater at a speed of 3000 rpm for 30 seconds, followed by pre-baking at 100°C on a hot plate for 60 seconds.

[0066] At this point, the unexposed film is easily soluble in nonpolar developers such as n-heptane, n-nonane, or cyclopentane.

[0067] (2) Pre-exposure treatment (pre-crosslinking): The film is fully exposed using an ultraviolet light source with a wavelength of 365nm and an irradiation intensity of 600mW / cm. 2 The irradiation time is 2 hours.

[0068] After pre-exposure, an initial cross-linking network is formed inside the film, which is completely insoluble in the non-polar developer.

[0069] (3) High-energy beam exposure treatment (de-crosslinking): The pre-crosslinked film is placed in an electron beam exposure system for regional exposure.

[0070] The test dose range is 0–3000 μC / cm. 2 .

[0071] A high-energy electron beam causes the chemical bonds in the exposed area to break, producing low-polarity small molecule fragments.

[0072] (4) Development: Immerse the silicon wafer in a non-polar developer (n-heptane) for 30 seconds and dry it with nitrogen.

[0073] As the exposed areas regain solubility and are washed away, the film exhibits typical positive lithography behavior (i.e., the exposed areas dissolve while the unexposed areas remain).

[0074] Performance evaluation: The samples were characterized using AFM to obtain... Figure 2 The exposure dose is shown as a step chart of the adhesive residue height.

[0075] Its characteristic is that as the exposure dose increases, the thickness of the residual photoresist continuously decreases until the film is completely removed, exhibiting typical positive photolithography features.

[0076] Normalized dose curve as follows Figure 3 As shown, the positive sensitivity can reach 220 μC / cm. 2 .

[0077] Its high-resolution positive lithography pattern, such as Figure 4 As shown, the extreme feature resolution reaches 40nm.

[0078] Mechanism verification: Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were performed on the thin films before and after high-energy beam exposure in Example 1. The results showed that the Sb-O bond signal, representing the pre-crosslinked network, was significantly weakened after high-energy beam exposure, and the characteristic absorption peak of the carbon-carbon double bond in the ligand (approximately 1630 cm⁻¹) was reduced. -1 The reappearance of the double bonds after high-energy beam exposure indicates that the double bonds consumed by cross-linking are released during the de-cross-linking process, directly proving the chemical mechanism by which the high-energy beam breaks the pre-cross-linked network and deconstructs the macromolecule.

[0079] Comparative Example 1: Conventional negative patterning process for mononuclear antimony complex Ph3Sb(CA)2 The operation was exactly the same as in Example 1, except that the pre-exposure treatment in step (2) was omitted. After spin coating, electron beam exposure and n-heptane development were performed directly. Due to the lack of a pre-crosslinked network, the film exhibited typical negative lithography behavior (i.e., crosslinking was retained in the exposed areas, while the unexposed areas dissolved).

[0080] Performance evaluation: (The following appears to be a separate, unrelated sentence fragment: "Obtaining...") Figure 5 The AFM step diagram shown is characterized by a continuous increase in resist height with increasing exposure dose until thickness saturation, exhibiting a negative lithography characteristic. The normalized dose curve is shown below. Figure 6 As shown, the negative sensitivity is 900 μC / cm. 2 Its high-resolution negative lithography pattern is as follows: Figure 7 As shown, the limiting feature resolution is only 100nm.

[0081] Comparison Conclusion: Figure 2 and Figure 5 , Figure 3 and Figure 6 It can be seen that the pre-exposure process successfully caused the polarity reversal of Ph3Sb(CA)2. (Comparison) Figure 4 and Figure 7 It can be seen that the positive lithography resolution (40nm) of Example 1 (the present invention) is significantly better than the negative resolution (100nm) of direct exposure.

[0082] Example 2: Positive patterning process of dinuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 (254nm pre-exposure) (1) Thin film preparation: The binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 containing photosensitive double bond ligands was dissolved in cyclohexanone to prepare a coating solution with a concentration of 20 mg / mL. The solution was uniformly spin-coated onto a clean silicon wafer using a spin coater at a speed of 2000 rpm for 20 s, and then preheated on a hot plate at 100 °C for 60 s.

[0083] (2) Pre-exposure treatment (pre-crosslinking): Ultraviolet light with a wavelength of 254nm (irradiation intensity 100mW / cm) was used. 2 The silicon wafer is pre-exposed (for 15 minutes) to transform the thin film into an insoluble state in a non-polar developer.

[0084] (3) High-energy beam exposure treatment (de-crosslinking): The electron beam exposure dose range is the same as in Example 1.

[0085] (4) Development: The developer is changed to n-nonane, and development is performed for 60 seconds.

[0086] Performance evaluation: obtained Figure 8 AFM adhesive retention ladder diagram and Figure 9 The dose curve confirmed positive photolithography, with a sensitivity of 980 μC / cm. 2 Its high-resolution positive pattern is as follows: Figure 10 As shown, the extreme feature resolution reaches 48nm.

[0087] Example 3: Positive patterning process of dinuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 (365nm pre-exposure) (1) Thin film preparation: The process is the same as in Example 2.

[0088] (2) Pre-exposure treatment (pre-crosslinking): changed to ultraviolet light with a wavelength of 365nm (irradiation intensity of 600mW / cm). 2 Pre-exposure was performed (for 1 hour), and the film was also transformed into an insoluble state.

[0089] (3) High-energy beam exposure treatment (de-crosslinking): The electron beam exposure dose range is the same as in Example 2.

[0090] (4) Development: The development operation with n-nonane is the same as in Example 2.

[0091] Performance evaluation: obtained Figure 11 AFM adhesive retention ladder diagram and Figure 12 The dose curve confirmed positive photolithography, with a sensitivity of 225 μC / cm. 2 High-resolution positive patterns, such as Figure 13 As shown, the extreme feature resolution reaches 46nm.

[0092] Comparative Example 2: Conventional negative patterning process for binuclear antimony oxide clusters (Ph3Sb)2(μ2-O)(MMA)2 The thin film preparation process is the same as in Examples 2 and 3. The pre-exposure step is completely omitted, and electron beam exposure and n-nonane development are performed directly.

[0093] Performance evaluation: obtained Figure 14 AFM adhesive retention ladder diagram and Figure 15 The dose curve confirmed negative photolithography, with a sensitivity of 11 μC / cm. 2 Its high-resolution negative patterns, such as Figure 16 As shown, the limiting feature resolution is only 160nm.

[0094] Comparative conclusion: The comparison shows that the method of the present invention achieves positive patterns of 46-48nm under electron beam exposure, while the negative process of direct exposure has a limit resolution of 160nm under the same material system.

[0095] Example 4: Positive patterning process for tetranuclear antimony oxide clusters (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2 (1) Thin film preparation: Tetranuclear antimony oxide cluster (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2 containing photosensitive double bond ligands was dissolved in PGMEA to prepare a coating solution with a concentration of 50 mg / mL. The solution was uniformly spin-coated onto a clean silicon wafer using a spin coater at a speed of 4000 rpm for 30 s, and then pre-baked on a hot plate at 110 °C for 60 s.

[0096] (2) Pre-exposure treatment (pre-crosslinking): Ultraviolet light with a wavelength of 254nm (intensity 100mW / cm²) was used. 2The silicon wafer is pre-exposed (for 15 minutes) to make the film insoluble.

[0097] (3) High-energy beam exposure treatment (de-crosslinking): The electron beam exposure dose range is the same as in Example 2.

[0098] (4) Development treatment: The developer was changed to cyclopentane and developed for 30 seconds.

[0099] Performance evaluation: obtained Figure 17 AFM adhesive retention ladder diagram and Figure 18 The dose curve confirmed positive photolithography, with a sensitivity of 350 μC / cm. 2 High-resolution positive patterns, such as Figure 19 As shown, the extreme feature resolution reaches 36nm.

[0100] Comparative Example 3: Conventional negative patterning process for tetranuclear antimony oxide clusters (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2 The thin film preparation process is the same as in Example 4. The pre-exposure step in Example 4 is completely omitted, and electron beam exposure and cyclopentane development are performed directly.

[0101] Performance evaluation: obtained Figure 20 AFM adhesive retention ladder diagram and Figure 21 The dose curve confirmed negative photolithography, with a sensitivity of 24 μC / cm. 2 Its high-resolution negative patterns, such as Figure 22 As shown, the limiting feature resolution is only 180nm.

[0102] Comparative conclusion: The comparison shows that the method of this invention achieves a 36nm positive pattern under EBL, while the direct exposure negative process has a limit resolution of 180nm under the same material system.

[0103] Example 5: Positive patterning process for mixed solvent systems (1) Thin film preparation: The mononuclear antimony complex Ph3Sb(CA)2 containing photosensitive double bond ligands was dissolved in a mixed solvent of PGMEA and cyclohexanone (volume ratio 1:1) to prepare a coating solution with a concentration of 20 mg / mL. The solution was uniformly spin-coated onto a clean silicon wafer using a spin coater at a speed of 3000 rpm for 30 s, and then pre-baked on a hot plate at 100 °C for 60 s.

[0104] (2) Pre-exposure treatment (pre-crosslinking): The film is fully exposed using an ultraviolet light source with a wavelength of 365nm and an irradiation intensity of 600mW / cm. 2 The irradiation time is 2 hours.

[0105] (3) High-energy beam exposure treatment (de-crosslinking): The electron beam exposure dose range is the same as in Example 1.

[0106] (4) Development: Immerse the silicon wafer in n-heptane for 30 seconds and dry it with nitrogen.

[0107] Performance evaluation: A positive photolithography pattern similar to that of Example 1 was obtained, with a sensitivity of 215 μC / cm. 2 The limiting feature resolution reaches 40nm, proving that the mixed solvent system is also applicable to the method of this invention and can effectively optimize the film quality.

[0108] Example 6: Plasma dry etching pattern transfer of patterned substrates and device structures Using the positively patterned thin film obtained in Example 1 as the physical mask, the underlying substrate was a silicon wafer with a silicon dioxide (SiO2) layer grown on its surface. The sample was placed in an inductively coupled plasma (ICP) etching machine for dry etching. A CF4 / CHF3 / Ar mixed gas was used as the etching gas, with the ICP RF power set to 500W, the bias power to 50W, and the reaction chamber pressure controlled at 1.5Pa. The etching process lasted 60 seconds. After etching, residual metal-organic mask was removed using wet cleaning (e.g., dilute hydrofluoric acid solution) combined with oxygen plasma ashing. X-ray photoelectron spectroscopy (XPS) analysis showed that the amount of residual antimony on the substrate surface after ash removal was below the process tolerance detection limit. Cross-sectional observation using scanning electron microscopy (SEM) confirmed that the photoresist pattern was transferred to the SiO2 layer with high fidelity, the etching depth reached 120nm, and the hole wall perpendicularity was good.

[0109] As a comparative example, commercial PMMA photoresist (molecular weight 950K) of the same thickness was tested under the same ICP dry etching conditions. The results show that the dry etching rate of the antimony-based photoresist mask of the present invention is approximately 34 nm / min, while the etching rate of the PMMA photoresist is approximately 119 nm / min. The dry etching resistance selectivity of the mask of the present invention is improved by approximately 3.5 times compared with the traditional commercial PMMA photoresist. Patterned substrates with high-resolution structures were successfully fabricated, verifying the feasibility of this mask in high etching resistance application in the fabrication of feature structures for semiconductor devices.

[0110] In some specific embodiments of this application, based on the aforementioned high-resolution positive photolithography pattern, a method for fabricating a patterned substrate and semiconductor devices is further provided, which includes the following steps: forming a positive patterned thin film on a substrate (such as a silicon wafer or a wafer with an oxide layer or nitride layer deposited on its surface) using the process of the present invention described in the above embodiments; subsequently, using the positive patterned thin film as a physical mask, transferring the pattern to the underlying substrate material with high fidelity through a plasma dry etching process, thereby obtaining the desired patterned substrate.

[0111] In this application embodiment, there is no limitation on the specific type of semiconductor device. Those skilled in the art can rely on the actual application needs, and after completing the aforementioned mask patterning and etching processes, perform subsequent semiconductor process steps on the patterned substrate to finally prepare the required semiconductor device.

[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0113] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended technical solutions and their equivalents.

Claims

1. A method for positive photoresist patterning based on pre-exposure control, characterized in that, Includes the following steps: Step 1, Thin film preparation: Dissolve an antimony-based organometallic compound containing photosensitive unsaturated double bond ligands in a coating solvent, coat it onto the substrate surface, and form a photoresist thin film after baking. The photosensitive unsaturated double bond ligand is a carboxylic acid ligand containing a carbon-carbon double bond; The carboxylic acid ligand containing a carbon-carbon double bond is selected from one or more of trans-cinnamic acid, methacrylic acid, acrylic acid, p-vinylbenzoic acid, crotonic acid, sorbic acid, furanylacrylic acid, or methoxycinnamic acid. The antimony-based organometallic compound is selected from one or more of the following: mononuclear antimony complex Ph3Sb(CA)2, binuclear antimony oxide cluster (Ph3Sb)2(μ2-O)(MMA)2 or tetranuclear antimony oxide cluster (Ph2Sb)4(μ2-O)4(μ2-OH)2(MMA)2; Step 2, Pre-exposure treatment: The photoresist film is fully pre-exposed using ultraviolet light with a wavelength in the range of 254nm to 400nm, which triggers the photosensitive unsaturated double bond ligand to undergo a photochemical reaction and form a pre-crosslinked network in the film, making the film substantially insoluble in non-polar developer. Step 3, High-energy beam exposure processing: Use a high-energy beam to expose a specific patterned area of ​​the photoresist film that has undergone the pre-exposure processing, so that the exposed area regains its solubility in the non-polar developer. The high-energy beam is an electron beam; or the high-energy beam is extreme ultraviolet light. Step 4, Development: The film exposed by the high-energy beam is developed using a non-polar developer. The areas exposed by the high-energy beam are dissolved, while the areas not exposed by the high-energy beam are retained, thereby obtaining a positive photolithography pattern.

2. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 1, the coating solvent is selected from one or more of methanol, isopropanol, N,N-dimethylformamide, acetone, ethyl acetate, propylene glycol methyl ether acetate, chloroform, cyclohexanone, or tetrahydrofuran.

3. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 1, the concentration of the antimony-based organometallic compound in the coating solvent is 15–100 mg / mL.

4. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 1, the spin coating speed is 500-5000 rpm and the spin coating time is 20-60 s; The baking process is carried out at a temperature of 80–150°C for 30–90 seconds.

5. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 2, the first wavelength is 254nm ultraviolet light, and the irradiation intensity is 50–200mW / cm². 2 The irradiation time is 0.1–0.5 hours; The first wavelength is 365nm ultraviolet light, and the irradiation intensity is 200-800mW / cm². 2 The irradiation time is 0.5 to 3 hours.

6. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 3, when the high-energy beam is an electron beam, the exposure dose of the electron beam is 100–3000 μC / cm. 2 ; The wavelength of the extreme ultraviolet light is 13.5 nm.

7. The photoresist positive patterning method based on pre-exposure control according to claim 1, characterized in that, In step 4, the nonpolar developing solution is selected from aliphatic hydrocarbon solvents, including one or more of n-heptane, n-nonane, or cyclopentane; The development time is 10–120 seconds.

Citation Information

Patent Citations

  • Organotin oxide hydroxide patterning compositions, precursors, and patterning

    US10228618B2

  • Metal oxygen cluster composition and photoetching patterning application

    CN117008416A

  • Positive photoresist composition and application thereof

    CN120447304A